Case Report on Modified Whale’s Tail Technique Using Amnion Membrane for Periodontal Regeneration in the Anterior Teeth with Diastema - Patil, Agraja Ganpat; Bhatt, Vaibhavi Hitesh (Highlights on Medicine and Medical Research Vol. 13, 2021)
The most difficult aspect of periodontal regeneration in the anterior region is maintaining esthetics. The Whale's Tail technique uses a new flap design that fulfils both of these goals while retaining the periodontal tissues' functional integrity. The main complaint of a 46-year-old man was gum bleeding. 11 has a probing pocket depth of 7 mm mesially and clinical attachment loss of 8 mm, according to his periodontal evaluation.The whale's tail technique was used in this case to obtain a 4mm gain in clinical attachment level after 11 months utilising demineralized freeze-dried bone allograft (DFDBA) and Amnion membrane. In diastema cases, this approach successfully exhibits stable clinical outcomes in terms of managing anterior periodontal regeneration. Validation of these results will require long-term clinical trials. Whale’s tail technique combines the advantages of papilla preservation in esthetic cases as well as facilitates access to the underlying alveolar bone for regenerative purposes.